Numerical investigation of turbulent forced convection heat transfer in pillow plates. (March 2016) - Piper, M.; Zibart, A.; Tran, J.M.; Kenig, E.Y.
Highlights: Accurate pillow plate geometry produced by forming simulations. A characteristic two-zone flow pattern in pillow plates was identified. The use of oval-form or reduced round-form welding spots increases the thermo-hydraulic efficiency. Abstract: Pillow-plate heat exchangers (PPHE) are characterized by the wavy "pillow-like" surface. Being a promising alternative to conventional equipment, they have recently received increased attention in the process industry. However, the knowledge on the flow and heat transfer characteristics in pillow-plate channels is scarce. Such knowledge is necessary for the development of successful design principles for PPHE. In this study, turbulent single-phase flow in pillow plates was investigated using CFD. The results for pressure loss and heat transfer coefficients were successfully validated against our own experiments. The simulations show that the flow in pillow plates is characterized by two distinct regions, namely a meandering core, which dominates heat transfer, and recirculation zones, which occur in the wake of the welding spots. The influence of the pillow-plate geometry on their thermo-hydraulic performance was also investigated, and the most favorable designs were identified. Based on the simulated flow field simple geometrical improvements are proposed, which significantly improve the thermo-hydraulic performance of pillow plates.